Y-chromosome STRs DYS385, DYS19, DYS389-I and II, DYS390, DYS391, DYS392 and DYS393 in five African populations - Lopes, V. (2003)
Background: The Y chromosome has been used to compare the relationship between populations, representing a rich source of potential information to trace paternal lineages and providing a record of our relatedness. Among different population groups, African populations seem to be very interesting to study, considering the theory of the origin of modern humans and the ethnic variability usually existing. Methods: Five male populations from Angola (n=48), Cap Verde (n=47), Guinea-Bissau (n=32), Mozambique (n=36) and S. Tome and Prince (n=30) were studied for Y-chromosome Short Tandem Repeats (STRs) DYS385, in addition to DYS19, DYS389-I and II, DYS390, DYS391, DYS392 and DYS393 previously searched. Results: The high DYS385 polymorphism confers a considerable variability to the Y-chromosome haplotype. Conclusions: The comparisons between the African populations and other data, namely from a Portuguese population, showed an interesting location of insular populations, with an intermediate position between Caucasoid and African continental populations, probably due to the European presence in the colonization of those islands.